Pengembangan bahan ajar dengan menggunakan pendekatan kontekstual berbantuan powerpoint geogebra pada materi bangun ruang sisi datar - Ridwan, Rendi A; Setiawan, Wahyu (IKIP Siliwangi, 2023)
This study aims to develop teaching materials assisted by PowerPoint Geogebra. This research is a development research (Reaserch and Development) with a 3D development model (Define, Design, Develop). The subjects of this study were class IX students of SMPN 5 Darangdan Purwakarta for limited trials and class VIII students for wide trials. Data analysis technique uses descriptive qualitative. The data that has been collected is then analyzed using Microsoft Excel. The results of the study on the feasibility of teaching materials were seen from the results of the assessment of lesson plans, worksheets, and media with a percentage of 93.80% and the results of assessments by two mathematics teachers with a percentage of 89%. Teaching materials were tested for practicality using a student response questionnaire with a percentage of 90%. Thus this teaching material can be implemented and can be used. The results of this study can be categorized as valid, practical, and very feasible because they have received a good due diligence.